Multivariate interactions of natural and anthropogenic factors on Cd behavior in arable soil. Issue 51 (6th May 2015) - Wang, Fangli; Ouyang, Wei; Hao, Fanghua; Critto, Andrea; Zhao, Xuchen; Lin, Chunye
Abstract : The effect of one natural factor was generally weakened by binary interactions, which were further weakened by ternary interactions. This significant effect was computed via design of experiments. Abstract : Multivariate interactions are far more complex between natural factors and pollutants resulting from anthropogenic practices than between pollutants themselves. But little attention has been focused on the complex interpretation of multivariate interactions. To bridge this research gap, this study aimed to identify the interactive effect of multiple affecting factors including freeze–thaw cycles (FT), soil water (SW) content, and chlorpyrifos (CP) on soil Cd behavior in arable soil, based on the analysis of changes in Cd fractionations and Cd availability. Moreover, the significant effect was computed via design of experiments. The content of Cd fractions and the evaluated index of Cd availability were obtained by employing the modified six-step sequential extraction method. The results showed that the main effect of FT, SW and CP on Cd fractionation and availability was significant. The binary interactions weakened the main effect of FT or SW, but enhanced the main effect of CP on Cd fractionation. The ternary interactions further weakened the binary interactions, whereas CP enhanced the interaction between SW and FT. The interaction between SW and CP had a negative effect on residual Cd, but positively affected water-soluble and organic matter-bound Cd. The binary interaction between CP and FT had a positive effect on residual Cd (21.0%), but negatively affected water-soluble and Fe–Mn-oxide-associated Cd (25.9% and 21.1%). These results covered more innovative information on the multivariate interactions between natural and anthropogenic factors on Cd behavior in arable soil. A possible new way to quantify the significant impact of multivariate factors also was provided.